Unstructured Peer-to-Peer Botnet Simulation for Measuring Its Robustness - Sayed Muchallil; Subhasish Dutta Chowdhuri; Kiran Venkatesh; Abhiram Doddaballapur Venkatraman; Candeep Singh (Universitas Syiah Kuala, 2011)
Malware attacks on the Internet have increasedsubstantially in recent years for which botnets are a root cause. A